On $σ$-subnormal subgroups of finite 3'-groups - Kamornikov, S. F.; Tyutyanov, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 512.542For a partition $σ$ of the set $\mathbb{R}$ of all primes, it is solved that if every complete Hall set of type $σ$ of a finite $3 ′$-group $G$ is reducible in some subgroup $H$ of $G$, then $H$ is $σ$ -subnormal in $G$.